Clinical and X-ray diagnostics of odontogenic cysts sinusalnyh rhino-inflammatory genesis (LLC "Endo Press", 2020)
The use of modern high-tech methods of beam diagnostics, such as digital orthopantomography, spiral and cone-beam computed tomography with dynamic densitometry, along with a detailed analysis of the clinical and histological data, can significantly improve the quality of assessment of the status of dental system, make a differential diagnosis between the types of cysts to analyze the extent of the pathological process of the surrounding tissue and to determine the best way to resembling surgery. Anatomical features of the upper jaw, namely the proximity of the roots of teeth to the walls of the maxillary sinus or nasal cavity, and sometimes localization of the roots of premolars and molars in the sinus cavity, causes the close relationship of these anatomical structures in the presence and spread of inflammation from the periapical region of the teeth in the nasal cavity or maxillary sinus. The important point is to assess the integrity of the bony walls of the nasal cavity or sinus, the state of the mucous membrane of upper respiratory tract, the presence or lack of communication between the cavity of the mouth and nose through the formed fistula. Detailed definition of the above signs of a significant impact on treatment selection and prognosis for recovery.